2020
DOI: 10.1093/ehjci/jeaa282
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic validation of partition values for quantitative parameters to grade functional tricuspid regurgitation severity by conventional echocardiography

Abstract: Aims Quantitative echocardiography parameters are seldom used to grade tricuspid regurgitation (TR) severity due to relative paucity of validation studies and lack of prognostic data. To assess the relationship between TR severity and the composite endpoint of death and hospitalization for congestive heart failure (CHF); and to identify the threshold values of vena contracta width (VCavg), effective regurgitant orifice area (EROA), regurgitant volume (RegVol), and regurgitant fraction (RegFr)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Although a mild degree of TR is frequent and benign, moderate and severe TR are associated with poor prognosis. 98,99 It should be stressed that TR is most often seen in patients with multiple valvular disease, especially aortic or MV disease.…”
Section: Tricuspid Regurgitationmentioning
confidence: 99%
“…Although a mild degree of TR is frequent and benign, moderate and severe TR are associated with poor prognosis. 98,99 It should be stressed that TR is most often seen in patients with multiple valvular disease, especially aortic or MV disease.…”
Section: Tricuspid Regurgitationmentioning
confidence: 99%
“…Accumulating evidence links EROA to outcome in various settings 22,23 and current American Society of Echocardiography (ASE) and European Association of Cardiovascular Imaging (EACVI) guidelines define severe TR as an EROA ≥0.40 cm 2 and RVol ≥45 mL 20,24 . However, since patients undergoing transcatheter TV interventions (TTVI) frequently have an anatomical regurgitant area several times greater than an EROA of 0.40 cm 2 , an extended classification to include "massive" and "torrential" TR (both associated with detrimental outcomes) has recently been proposed (Supplementary Table 1) [23][24][25][26][27] .…”
Section: Definition Of Disease Severitymentioning
confidence: 99%
“…Some studies demonstrated that FTR severity was associated with worse outcome. During 47-month follow-up, Muraru et al showed that event-free rate was 14%, 48%, and 93% in patients with severe, moderate, and mild FTR, respectively [ 2 ]. Event was defined as death or occurrence of heart failure.…”
Section: The Predictive Value Of Ftrmentioning
confidence: 99%
“…In the last decade, our knowledge about TV anatomy, morphology, and function significantly increased due to enormous development of imaging techniques and primarily three-dimensional echocardiography (3DE) [1]. At the same time, growing data of evidence revealed the importance of functional tricuspid regurgitation (FTR) on the outcome in patients with different cardiovascular diseases (CVD) including concomitant valvular disease (aortic stenosis, mitral regurgitation), heart failure, pulmonary hypertension, and even in patients without evident CVD [2][3][4][5]. Figure 1 illustrates difference in etiologies that lead to primary (organic) and secondary (functional) tricuspid regurgitation.…”
Section: Introductionmentioning
confidence: 99%